2009
DOI: 10.1097/rli.0b013e3181ae9c40
|View full text |Cite
|
Sign up to set email alerts
|

Relative Recirculation

Abstract: Both KPS and rR are significantly elevated in infarcted, relative to uninfarcted tissue in the same AIS patient. Both parameters were also significantly elevated in HT, relative to non-HT infarcts. The strong correlation between rR and KPS, coupled with the high sensitivity and specificity of rR for the prediction of HT suggest that rR is related to blood-brain barrier integrity in AIS and may prove valuable in the prediction of HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…(Jin et al, 2012) Animal and human studies found that thrombolysis-associated cerebral hemorrhage occurred in the brain regions where the BBB was compromised. (Bang et al, 2007; Hjort et al, 2008; Hom et al, 2011; Kassner et al, 2009; Sun et al, 2010; Wu et al, 2009) These studies suggest that loss of BBB integrity during cerebral ischemia may predispose ischemic brain tissue to bleeding during reperfusion with thrombolysis. In middle cerebral artery occlusion (MCAO) model, dextran leaks in the ischemic ventromedial striatum and the preoptic area, where high (2000 kDa) and low (70 kDa) molecular weight dextrans displayed almost identical leakage patterns.…”
Section: Introductionmentioning
confidence: 93%
“…(Jin et al, 2012) Animal and human studies found that thrombolysis-associated cerebral hemorrhage occurred in the brain regions where the BBB was compromised. (Bang et al, 2007; Hjort et al, 2008; Hom et al, 2011; Kassner et al, 2009; Sun et al, 2010; Wu et al, 2009) These studies suggest that loss of BBB integrity during cerebral ischemia may predispose ischemic brain tissue to bleeding during reperfusion with thrombolysis. In middle cerebral artery occlusion (MCAO) model, dextran leaks in the ischemic ventromedial striatum and the preoptic area, where high (2000 kDa) and low (70 kDa) molecular weight dextrans displayed almost identical leakage patterns.…”
Section: Introductionmentioning
confidence: 93%
“…For example, measurements derived from the relative-recirculation method were shown to correlate significantly with K trans values derived from a Patlak model applied to DCE-MRI. 39 In the clinical setting, the availability and speed of CT make it the modality of choice when making treatment decisions for AIS. [41][42][43][44] BBB disruption can potentially be assessed by incorporating a DCE-CT protocol into the initial CT imaging of a patient with AIS.…”
Section: Strokementioning
confidence: 99%
“…39,40 Model-free approaches simplify data analysis and may therefore be easier to incorporate into a clinical setting. For example, measurements derived from the relative-recirculation method were shown to correlate significantly with K trans values derived from a Patlak model applied to DCE-MRI.…”
Section: Strokementioning
confidence: 99%
“…1114 This concern is emphasized in several scientific articles and might lead physicians to forego tPA treatment, even when appropriate. Although logistical and diagnostic delays are important roadblocks to care, physician fear of hemorrhage remains a major obstacle to tPA treatment for ischemic stroke.…”
mentioning
confidence: 99%